2017
DOI: 10.1002/jbm.b.33872
|View full text |Cite
|
Sign up to set email alerts
|

Laser surface modification of 316L stainless steel

Abstract: Medical grade 316L stainless steel was laser surface melted (LSM) using continuous wave Nd-YAG laser in argon atmosphere at 1 and 5 mm/s. The treated surfaces were characterized using electron backscatter diffraction to study the influence of top surface crystallographic orientation and type of grain boundaries on corrosion resistance, wettability, and biocompatibility. The laser scan velocity was found to have a marginal influence on the surface roughness and the type of grain boundaries. However, the crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…31 The role of texture on corrosion resistance in laserprocessed SS has been explored in several laser surface melting (LSM) studies, but with conflicting findings. [32][33][34][35] Close analysis of several of these studies suggests that reported trends in corrosion resistance as a function of texture, for example, were confounded by differences in distributions of δ-ferrite, nonmetallic inclusions, and grain boundary nature imparted by the different processing conditions used to achieve the textures. 32 In other words, crystallographic texture can often be secondary to stronger corrosion-inducing features, which is important given the controlling role of defects in in the corrosion of AM SS as will be discussed later.…”
Section: Texturementioning
confidence: 99%
“…31 The role of texture on corrosion resistance in laserprocessed SS has been explored in several laser surface melting (LSM) studies, but with conflicting findings. [32][33][34][35] Close analysis of several of these studies suggests that reported trends in corrosion resistance as a function of texture, for example, were confounded by differences in distributions of δ-ferrite, nonmetallic inclusions, and grain boundary nature imparted by the different processing conditions used to achieve the textures. 32 In other words, crystallographic texture can often be secondary to stronger corrosion-inducing features, which is important given the controlling role of defects in in the corrosion of AM SS as will be discussed later.…”
Section: Texturementioning
confidence: 99%
“…3,4 For example, implantable SS devices may release chromium and nickel ions, which becomes a barrier to their widespread use in the medical industry due to the potential for chronic inflammation and toxicity. 5 Currently, different surface modification approaches have been reported to decrease the release of metallic ions, such as nitrogen implantation, 6 laser surface modification, 7 and plasma polymerization. 8−12 Among them, the deposition of organosilicon coatings on the surface of metal implants by plasma polymerization technology is a promising surface modification method for metal biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, different surface modification approaches have been reported to decrease the release of metallic ions, such as nitrogen implantation, laser surface modification, and plasma polymerization. Among them, the deposition of organosilicon coatings on the surface of metal implants by plasma polymerization technology is a promising surface modification method for metal biomaterials. One of the most representative methods was plasma-enhanced chemical vapor deposition (PECVD), which made it possible to create homogeneous thin films with a higher density on a variety of substrates at a relatively low temperature . In addition, the plasma-polymerized (pp) organosilicon films on metal substrates generally form an excellent hydrophobic barrier and have excellent mechanical properties and scratch resistance …”
Section: Introductionmentioning
confidence: 99%
“…Despite the advantages presented some care must be taken to apply components manufactured by WAAM, since the high energy rate (between 1000 and 3000 W [4]) characteristic of these processes can result in non-homogeneous parts with anisotropic microstructure [9]- [11]. Balla et al [12] report the importance of controlling the microstructure of the material, since important properties of crystalline materials, such as: mechanical behavior; deformation and fracture are strongly in uenced by crystallographic orientation and texture. The thermodynamic non-equilibrium that occurs in the complex thermal cycle of wire arc additive manufacturing would be responsible for these changes in the material, since each layer of the deposited is subjected to different heating and cooling conditions [9], [13], [14].…”
Section: Introductionmentioning
confidence: 99%